Molecules sensing layer design of piezoresistive cantilever sensor for higher surface stress sensitivity - Yin, Tsung-I; Nguyen, Tien Anh (Vietnam Journal of Mechanics, 2012)
This paper reports on molecular sensing layer design of a piezoresistive cantilever sensor for higher surface stress sensitivity. The proposed analyses show that the previous understanding of piezoresistive cantilevers for surface stress measurement requires reconsideration for a cantilever utilizing polycrystalline silicon as a piezoresistor. The integration of the molecular sensing layer stripe pattern design to the cantilever effectively improves the piezoresistive output and utilizes the full sensing area of the cantilever surface. The proposed sensing layer design can be effectively integrated to current piezoresistive cantilever sensors to improve sensor performance in biochemical assays.